engaruh Digital Marketing Dan Penilaian Pelanggan Terhadap Keputusan Pembelian Dengan Keterlibatan Pelanggan Sebagai Variabel intervening (Studi Pada Situs Jual Beli Online Berrybenka) - Sindy Ameliya; Suwarto; Sri Retnaning Rahayu (Jurnal Manajemen DIVERSIFIKASI, 2025)
E-commerce is a sales system that developed after the invention of the Internet. A marketing or sales system like this can reach the whole world at the same time without having to set up branch offices in all countries. In addition, it can also be done 24 hours without stopping. Only through a computer connected to the Internet, companies can market their products. 1) This study aims to find out whether digital marketing has a direct effect on purchasing decisions on the berry benka e-commerce website? 2) Do customer ratings have a direct effect on purchasing decisions on the Berrybenka e-commerce website? 3) Does digital marketing have a direct effect on customer involvement on the Berrybenka e-commerce website? 4) Do customer ratings have a direct effect on customer engagement on the berrybenka e-commerce website? 5) Does customer involvement and customer assessment have a direct effect on purchasing decisions on the Berrybenka e-commerce website? The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire instrument or questionnaire. In this study, the population is consumers who use telkom products. The sampling technique uses accidental sampling with a total sample of 100 people. Data collection techniques using a questionnaire with a Likert scale. The results of the study show that 1) there is a positive and significant influence between digital marketing on purchasing decisions. 2) there is a positive and significant influence between the customer's assessment of the Purchase Decision. 3) there is a positive and significant influence between digital marketing on customer engagement 4) there is a positive and significant influence between customer ratings there is a positive and significant effect between product variations on customer engagement there is 5) a positive and significant effect between customer engagement and ratings customers on purchasing decisions